Analisis Tentang Penerapan Kurikulum 2013 Pada Mata Pelajaran Aqidah Akhlak - Mukni'ah, Mukni'ah (Universitas Muhammadiyah Magelang, 2019)
Curriculum is an important part of the implementation of learning in school. It covers the aspects of planning, implementation, and evaluation of learning. This study aims to describe the problems of planning, implementing, and evaluating the 2013 curriculum in the subjects of Aqidah Akhlak in MTs. Negeri 04 Jember. The method used in this study is descriptive qualitative with the type of field research. The data collection method used observation, interviews, and documentation. Data analysis used qualitative descriptive analysis of interactive models of Miles and Huberman. The results showed that the problems in planning, learning, and evaluating the 2013 curriculum in the Aqeedah Akhlak subjects were the difficulties faced by teachers in developing lesson plans and determining learning methods, mismatches between lesson plans and learning implementation, and constructing the score rubrics for attitude assessment.